1983
DOI: 10.1002/tea.3660200706
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of science classes taught by males and females

Abstract: In their analysis of National Assessment results Haertel et a1.t found that 13 year-old boys and girls are quite similar in science learning. However, this similarity does not exist for 17 year olds. One possible cause for this change is socio-cultural pressures. In this study, we suggest that the science classroom learning environment may contribute to these pressures due to differences in classes taught by male and female science teachers. The Learning Environment Inventory was used to assess student percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Girls and boys enter science classrooms with genderrelated attitudes (Reid & Stephens, 1985;Jones & Wheatly, 1988;Mason, Kahle & Gardner;1991). Boys react positively to careers in science, whereas girls tend to reject science-related careers for themselves and for their future husbands (Mead and Metraux 1957;Lawrenz and Welch, 1983;Wheatly, ISSN 1648-3898 1988). However, research does suggest that girls are more likely to pursue a scientific career when they receive positive messages from parents, teachers, counsellors, and peers, when they are exposed to positive role models, and when they expect to succeed (Jones & Wheatly, 1988;Huber & Burton, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Girls and boys enter science classrooms with genderrelated attitudes (Reid & Stephens, 1985;Jones & Wheatly, 1988;Mason, Kahle & Gardner;1991). Boys react positively to careers in science, whereas girls tend to reject science-related careers for themselves and for their future husbands (Mead and Metraux 1957;Lawrenz and Welch, 1983;Wheatly, ISSN 1648-3898 1988). However, research does suggest that girls are more likely to pursue a scientific career when they receive positive messages from parents, teachers, counsellors, and peers, when they are exposed to positive role models, and when they expect to succeed (Jones & Wheatly, 1988;Huber & Burton, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of subject-matter differences in classroom environment (Anderson, 1971;Kuert, 1979;Steele et aI., 1974) revealed several interesting contrasts: convergence---divergence contrasted mathematics (more convergent) with language arts (more divergent); substance-syntax contrasted science and social studies (focus more on substance) with language arts and mathematics (focus more on syntax); and objectivity-subjectivity contrasted science (more objective) with social studies (more subjective). Lawrenz and Welch (1983) have provided evidence that, in comparison with classes taught by male teachers, classes taught by female teachers were perceived by students to have more goal direction, formality and friction but less difficulty. Other research has revealed interesting differences between classes in different types of school (Trickett, 1978), in coeducational and singlegender schools (Trickett et aI., 1982) and in classes of teachers with different student control ideologies (Harty and Hassan, 1983).…”
Section: Evaluation Of Curricula and Innovationsmentioning
confidence: 94%
“…Stein and Bailey (1973) found that girls were more likely than boys to avoid tasks that were labeled "difficult." The view that science is "difficult," in combination with science's reputation for being stereotypically "masculine" may limit women's perceptions of success in science (Lawrenz & Welch, 1983).…”
Section: Expectations For Successmentioning
confidence: 99%